THE INFLUENCE OF GOOD CORPORATE GOVERNANCE AND SUSTAINABILITY AUDITS ON THE IMPLEMENTATION OF SDGS IN PUBLIC COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Rina Ambarwati; Abu Naim; Andika Mugi Gumilang; Ervina Yennie Permananingrum; Ahmad Pauji; Ilwin Hadi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The implementation of Sustainable Development Goals (SDGs) in public companies in Indonesia is becoming increasingly demanded as attention to sustainability issues grows. However, not all companies are able to optimally integrate the SDGs. This issue raises questions about the factors influencing the level of SDG implementation, particularly the role of Good Corporate Governance (GCG) and sustainability audits. This research aims to analyze the influence of GCG and sustainability audits on the implementation of SDGs in public companies listed on the Indonesia Stock Exchange. The research method uses a quantitative approach with purposive sampling technique and a total of 100 respondents from management and staff related to company sustainability. Data were analyzed using SPSS thru validity testing, reliability testing, classical assumptions testing, multiple linear regression, and hypothesis testing (t-test and F-test). The research results indicate that GCG and sustainability audits simultaneously have a positive and significant effect on the implementation of SDGs, with a contribution of 61.2%. Partially, both variables also have a significant effect. This finding confirms that strengthening good corporate governance and conducting credible sustainability audits are important strategies for improving the successful implementation of SDGs in public companies in Indonesia.